The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1051/0004-6361:20034509
|View full text |Cite
|
Sign up to set email alerts
|

Puzzling wind properties of young massive stars in SMC-N81

Abstract: Abstract. We present a quantitative study of massive stars in the High Excitation Blob N81, a compact star forming region in the SMC. The stellar content was resolved by HST, and STIS was used to obtain medium resolution spectra. The qualitative analysis of the stellar properties presented in Heydari-Malayeri et al. (2002a) is extended using non-LTE spherically extended atmosphere models including line-blanketing computed with the code CMFGEN (Hillier & Miller 1998), and the wind properties are investigated. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
109
2
1

Year Published

2006
2006
2011
2011

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(127 citation statements)
references
References 61 publications
15
109
2
1
Order By: Relevance
“…The calculations of Aerts et al (2004) match the observed mass-loss rates for Car, which has a peak of 1:6 AE 0:3 ð Þ; 10 À3 M yr À1 (assuming spherical symmetry) during normal outbursts, falling to 10 À5 M yr À1 during the intervening 5.5 yr (van Boekel et al 2003). For young (P4 Myr) O stars in the small Magellanic cloud, low (P10 À8 M yr À1 ) mass-loss rates were observed ( Martins et al 2004), indicating that massive stars may have much lower mass-loss rates until they approach the end of their main-sequence lifetimes (see Meynet & Maeder 2003).…”
Section: Evolution Of the Merger Productsupporting
confidence: 65%
“…The calculations of Aerts et al (2004) match the observed mass-loss rates for Car, which has a peak of 1:6 AE 0:3 ð Þ; 10 À3 M yr À1 (assuming spherical symmetry) during normal outbursts, falling to 10 À5 M yr À1 during the intervening 5.5 yr (van Boekel et al 2003). For young (P4 Myr) O stars in the small Magellanic cloud, low (P10 À8 M yr À1 ) mass-loss rates were observed ( Martins et al 2004), indicating that massive stars may have much lower mass-loss rates until they approach the end of their main-sequence lifetimes (see Meynet & Maeder 2003).…”
Section: Evolution Of the Merger Productsupporting
confidence: 65%
“…At the moment, the nature of this weak-wind problem eludes us; for a discussion we refer to e.g. Martins et al (2004), Martins et al (2005), de Koter (2006), Table 2. Adopted model parameters together with predicted mass loss rates for two clumping stratifications and porosity descriptions.…”
Section: The Weak-wind Problemmentioning
confidence: 99%
“…Observational studies consider the turbulence already present in the photospheres of O stars (e.g., Bouret et al 2003Bouret et al , 2005Martins et al 2004Martins et al , 2005 with turbulent velocities of about 2−25 km s −1 . Macroturbulent velocities in B supergiants may be even higher, about 30−100 km s −1 (Howarth et al 1997;Markova & Puls 2008).…”
Section: Models With Base Turbulencementioning
confidence: 99%
“…On the other hand, the modified ionization equilibrium may affect the X-ray line formation (Oskinova et al 2006;Krtička & Kubát 2009), and too ling cooling time in the post-shock region (Cohen et al 2008;Krtička & Kubát 2009) may cause the so-called "weak wind problem" (Bouret et al 2003;Martins et al 2004;Marcolino et al 2009). …”
Section: Introductionmentioning
confidence: 99%